2018
DOI: 10.1186/s12917-018-1657-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain and short-term complications after two elective sterilization techniques: ovariohysterectomy or ovariectomy in cats

Abstract: BackgroundSurgical sterilization of cats is one of the most commonly performed procedures in veterinary practice and it can be accomplished by two different techniques: ovariohysterectomy (OVH) or ovariectomy (OVE). Although there is an apparent preference for OVH in United States and Canada, OVE seems to be the standard of care in many European countries due to its advantages, such as a smaller surgical incision and potentially less complications associated with surgical manipulation of the uterus. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
0
19
1
6
Order By: Relevance
“…This could be related to the healthy study population, to the low postoperative pain level of ovariectomy or to the surgery analgesic protocol. 41 While no significant differences were found between pain scores in the present study, it is not possible to rule out the connection between gabapentin's positive effect on appetite and its analgesic properties.…”
Section: Discussioncontrasting
confidence: 81%
“…This could be related to the healthy study population, to the low postoperative pain level of ovariectomy or to the surgery analgesic protocol. 41 While no significant differences were found between pain scores in the present study, it is not possible to rule out the connection between gabapentin's positive effect on appetite and its analgesic properties.…”
Section: Discussioncontrasting
confidence: 81%
“…Ovariohysterectomy is one of the most common surgeries in small animals (Campagnol et al, 2012;Carpenter et al, 2004;Guerrero et al, 2016). Among the upsides of this surgery, mention can be made of population control, prevention of diseases related to the reproductive system and decrease in the unpleasant behaviours associated with sex hormones (Pereira et al, 2018). Ovariohysterectomy is classified as a major surgery (Hardie et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There were also no trans operative complications. In studies of OH in cats, the results were similar with no bleeding and trans operative complications 1,4 . The comparison of surgical times between the techniques used showed that KG had a statistically significant shorter surgical time compared to CG.…”
Section: Discussionmentioning
confidence: 57%
“…The queens were randomly distributed into three groups of seven. The female cats in the first group (CG) were operated using common suture thread (polyglactin 910) to perform OAVC ligature, this is the conventional technique 1 , 4 . The second group (KG) were operated using the knotting technique, in which the ovarian vessels were occluded by knotting the OAVC itself 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation